Density Functional Theory Study on the Adsorption Mechanism of Sulphide Gas Molecules on α-Fe2O3(001) Surface - Li Zhou (MDPI AG, 2021)
Sulphide gas is an impurity that affects the quality of natural gas, which needs reasonable storage and transportation. In this work, we investigated the adsorption structure and electronic behavior of hydrogen sulfide (H2S), carbonyl sulfur (COS), and methyl mercaptan (CH3SH) on sulphide gas molecules on pure and vacant α-Fe2O3(001) surfaces by density functional theory with geometrical relaxations. The results show that H2S and CH3SH are mainly adsorbed in the form of molecules on the pure Fe2O3(001) surface. On the vacant α-Fe2O3(001) surface, they can be adsorbed on Fe atoms in molecular form and by dissociation. The absolute value of the adsorption energy of H2S and CH3SH on the vacancy defect α-Fe2O3 surface is larger, and the density of states show that the electron orbital hybridization is more significant, and the adsorption is stronger. The charge differential density and Mulliken charge population analysis show that the charge is rearranged and chemical bonds are formed. The affinity of H2S to the vacancy α-Fe2O3(001) surface is slightly higher than that of CH3SH, while COS molecules basically do not adsorb on the α-Fe2O3(001) surface, which may be related to the stable chemical properties of the molecules themselves.